Global Finite-Time Stabilization for a Class of Uncertain High-Order Nonlinear Systems - Jian Wang; Jing Xie; Fangzheng Gao (Abstract and Applied Analysis)
This paper addresses the problem of global finite-time stabilization by state feedback for a class of high-order nonlinear systems under weaker condition. By using the methods of adding a power integrator, a continuous state feedback controller is successfully constructed to guarantee the global finite-time stability of the resulting closed-loop system. A simulation example is provided to illustrate the effectiveness of the proposed approach.